Enriched Environment Shortens the Duration of Action Potentials in Cerebellar Granule Cells - Eshra, Abdelmoneim; Hirrlinger, Petra; Hallermann, Stefan (Frontiers in Cellular Neuroscience, 2019)
Environmental enrichment for rodents is known to enhance motor performance. Structural and molecular changes have been reported to be coupled with enriched environment, but functional alterations of single neurons remain elusive. Here, we compared mice grown up under control conditions and enriched environment. We tested the motor performance on a rotarod and subsequently preformed whole cell patch clamp recordings in cerebellar slice focusing on granule cells of lobule IX, which is known to receive vestibular input. Mice grown up in an enriched environment stayed longer on an accelerating rotarod. Electrophysiological analyses revealed normal passive properties of granule cells and a functional adaptation to the enriched environment, manifested in faster action potentials with more depolarized voltage threshold and larger action potential overshoot. Furthermore, the maximal firing frequency of action potentials was higher in mice grown up in an enriched environment. These data show that enriched environment causes specific alterations in the biophysical properties of neurons. Furthermore, we speculate that the ability of cerebellar granule cells to generate higher firing frequencies improves motor performance.